Antibiotic associated diarrhea in outpatient pediatric antibiotic therapy - Sevgen Tanır Basaranoğlu; Ayşe Karaaslan; Enes Salı; Ergin Çiftçi; Zeynep Gökçe Gayretli Aydın; Bilge Aldemir Kocabaş; Cemil Kaya; Semra Şen Bayturan; Soner Sertan Kara; Dilek Yılmaz Çiftdoğan; Ümmühan Çay; Hacer Gundogdu Aktürk; et al. (BMC, 2023)
Abstract Background Antibiotic-associated diarrhea is one of the most frequent side effects of antimicrobial therapy. We assessed the epidemiological data of antibiotic-associated diarrhea in pediatric patients in our region. Methods The prospective multi-center study included pediatric patients who were initiated an oral antibiotic course in outpatient clinics and followed in a well-established surveillance system. This follow-up system constituded inclusion of patient by the primary physician, supply of family follow-up charts to the family, passing the demographics and clinical information of patient to the Primary Investigator Centre, and a close telephone follow-up of patients for a period of eight weeks by the Primary Investigator Centre. Results A result of 758 cases were recruited in the analysis which had a frequency of 10.4% antibiotic-associated diarrhea. Among the cases treated with amoxicillin-clavulanate 10.4%, and cephalosporins 14.4% presented with antibiotic-associated diarrhea. In the analysis of antibiotic-associated diarrhea occurrence according to different geographical regions of Turkey, antibiotic-associated diarrhea episodes differed significantly (p = 0.014), particularly higher in The Eastern Anatolia and Southeastern Anatolia. Though most commonly encountered with cephalosporin use, antibiotic-associated diarrhea is not a frequent side effect. Conclusion This study on pediatric antibiotic-associated diarrhea displayed epidemiological data and the differences geographically in our region.